Measurement of HLA class I expression in ankylosing spondylitis. Issue 10 (October 1992) - Creamer, P; Edmonds, J; Sullivan, J; Matthews, S
Abstract : The importance of HLA-B27 in the pathogenesis of ankylosing spondylitis is uncertain: current evidence favours a role for the B27 molecule itself. The possibility that quantitative differences in HLA-B27 expression may exist between patients with ankylosing spondylitis, family members, and control subjects positive for B27 was examined using appropriate monoclonal antibodies, flow cytometry, and a 'model lymphocyte' coated with a known number of mouse immunoglobulin binding sites. No differences were found between the groups. HLA-A2, examined for comparison, was expressed in greater amounts than HLA-B27, but each contributed only 10-20% of the total class I antigens. Homozygotes expressed twice the amount of antigen expressed by heterozygotes. Synovial lymphocytes expressed more class I antigens than peripheral lymphocytes.